Characterization of ginsenoside materials by EDAX. (2021) - Pandian, R.; Lalitha Kumari, S.
Abstract: In this work Creatine kinase (CK), also known as creatine phosphokinase (CPK) or phosphocreatine kinase, is an enzyme expressed by various tissues and cell types. The weight and atomic are found by using EDX method. In this work ck images are decomposed and encoding methods are used. The proposed algorithms are evaluated by PSNR, Compression ratio, Means square error and bits per pixel. The best compression algorithm is also found based, on the results obtained. So as to characterize the ck image the features are extracted and it is proven that after compression, the ck images show its ability for identifying types of defects. The results are an indicator to the promising application of this for medical image compression schemes.